PERBANDINGAN ANTARA FAKTOR RISIKO INFEKSI SALURAN KEMIH TERHADAP KEJADIAN KETUBAN PECAH DINI PRETERM DAN KETUBAN PECAH DINI ATERM - Latviya Rahmani Husein P (FK IK UMY 2016, 2016)
Background: Premature rupture of membran is one of many complications of pregnancy that lead to maternal deaths and reduce the Maternal Mortality Rate (MMR) . One of the causes of premature rupture of membranes is an urinary tract infection. Objective: The purpose of this study was to compare the number of urinary tract infection incidence between Preterm Premature Rupture of Membranes (PPROM) and Premature Rupture of Membranes (PROM). Methods: This study used comparative analytical observation with cross-sectional study design. The samples in this study were medical records of birth mothers with premature rupture of membranes (Preterm and at Term) in Sadewa Women and Children Hospital, Babarsari in 2014. Sampling was conducted by purposive sampling method with 64 samples which is divided into two groups: PROM and PPROM, with 32 samples for each. Data is analyzed using Chi-square test. Results: The result showed that there were no significant correlation of urinary tract infection as risk factor between Premature Rupture of Membranes (PROM) and Preterm Premature Rupture of Membranes (PPROM) with value of p>0,05 which is 0.266. Beside, the value of RR is 1,571 CI (0,698 - 3,536). Result of RR> 1 means that urinary tract infection in term pregnancies has more risk lead to Premature Rupture Membranes (PROM) 1,571 times compared to Preterm Premature Rupture of Membranes (PPROM). Conclusion: Based on the results, it can be concluded that there were no significant correlation between the incidence of urinary tract infections with premature rupture of membranes. There is comparison of the incidence of urinary tract infections between Premature Rupture of Membranes (PROM) and Preterm Premature Rupture of Membranes(PPROM) which is Premature Rupture of Membranes (PROM) has more urinary tract infection risk compared to Preterm Premature Rupture of Membranes (PPROM) in Sadewa Women and Children Hospital, Babarsari. Keywords: Urinary Tract Infection, Premature Rupture of Membranes, at Term, Preterm.